Facet‐Independent Electric‐Field‐Induced Volume Metallization of Tungsten Trioxide Films. Issue 26 (9th May 2016) - Altendorf, Simone G.; Jeong, Jaewoo; Passarello, Donata; Aetukuri, Nagaphani B.; Samant, Mahesh G.; Parkin, Stuart S. P.
Abstract : Reversible metallization of band and Mott insulators by ionic‐liquid gating is accompanied by significant structural changes. A change in conductivity of seven orders of magnitude at room temperature is found in epitaxial films of WO3 with an associated monoclinic‐to‐cubic structural reorganization. The migration of oxygen ions along open volume channels is the underlying mechanism.